Neuronal SIRT1 (Silent Information Regulator 2 Homologue 1) Regulates Glycolysis and Mediates Resveratrol-Induced Ischemic Tolerance. Issue 11 (November 2017) - Koronowski, Kevin B.; Khoury, Nathalie; Saul, Isabel; Loris, Zachary B.; Cohan, Charles H.; Stradecki-Cohan, Holly M.; Dave, Kunjan R.; Young, Juan I.; Perez-Pinzon, Miguel A.
Abstract : Background and Purpose—: Resveratrol, at least in part via SIRT1 (silent information regulator 2 homologue 1) activation, protects against cerebral ischemia when administered 2 days before injury. However, it remains unclear if SIRT1 activation must occur, and in which brain cell types, for the induction of neuroprotection. We hypothesized that neuronal SIRT1 is essential for resveratrol-induced ischemic tolerance and sought to characterize the metabolic pathways regulated by neuronal Sirt1 at the cellular level in the brain. Methods—: We assessed infarct size and functional outcome after transient 60 minute middle cerebral artery occlusion in control and inducible, neuronal-specific SIRT1 knockout mice. Nontargeted primary metabolomics analysis identified putative SIRT1-regulated pathways in brain. Glycolytic function was evaluated in acute brain slices from adult mice and primary neuronal-enriched cultures under ischemic penumbra-like conditions. Results—: Resveratrol-induced neuroprotection from stroke was lost in neuronal Sirt1 knockout mice. Metabolomics analysis revealed alterations in glucose metabolism on deletion of neuronal Sirt1, accompanied by transcriptional changes in glucose metabolism machinery. Furthermore, glycolytic ATP production was impaired in acute brain slices from neuronal Sirt1 knockout mice. Conversely, resveratrol increased glycolytic rate in a SIRT1-dependent manner and under ischemic penumbra-like conditions in vitro. Conclusions—: Our data demonstrate that resveratrol requires neuronal SIRT1 to elicit ischemic tolerance and identify a novel role for SIRT1 in the regulation of glycolytic function in brain. Identification of robust neuroprotective mechanisms that underlie ischemia tolerance and the metabolic adaptations mediated by SIRT1 in brain are crucial for the translation of therapies in cerebral ischemia and other neurological disorders. Abstract : Supplemental Digital Content is available in the text.